1980
DOI: 10.1002/1097-0142(19800715)46:2<355::aid-cncr2820460224>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analyses of human chorionic gonadotropin and its subunits produced by malignant tumors

Abstract: Human chorionic gonadotropin (hCG) and its subunits in plasma, urine, ascites, and tumor extracts from four patients with hCG-producing tumors (undifferentiated cell carcinoma and choriocarcinoma of the bladder, malignant teratoma of the retroperitoneum, and pancreatic carcinoma) were measured by the radioimmunoassays specific to each component. While both free alpha and beta subunits as well as the whole molecule of hCG were found in all these samples, the proportion of beta subunit was much higher in these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…This is in agreement with the findings of Cowley et al (1985). The hCG-like material isolated from serum and urine of patients with bladder cancer has also been shown to consist mainly of free beta subunit, though smaller molecular weight forms have been noted in urine (Hattori et al, 1980;Norman et al, 1985;Rodenburg et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the findings of Cowley et al (1985). The hCG-like material isolated from serum and urine of patients with bladder cancer has also been shown to consist mainly of free beta subunit, though smaller molecular weight forms have been noted in urine (Hattori et al, 1980;Norman et al, 1985;Rodenburg et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have given evidence for a disparity between the forms of human choriogonadotropin (hCG)' trophoblast (1)(2)(3)(4)(5)(6)(7). The abnormal forms of hCG and their metabolites are of clinical interest as potential molecular markers of the malignant transformation of the trophoblast.…”
Section: Introductionmentioning
confidence: 64%
“…Some of these forms of the hormone appear to be subunits of hCG (1)(2)(3)(4)(5)(6)(7), and some appear to be fragments, as they exhibit molecular sizes smaller than those of the hCG subunits (1,5,6,(8)(9)(10)(11). When obtained from different sources, hCG itself has been found to have variable biological, physicochemical, and immunological properties; this microheterogeneity seems to be related, in part, to variations in its carbohydrate composition (10,(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Fragments of this type have been observed in the urine of pregnant women (5,6,8,9), in crude commercial preparations of hCG from pregnancy (16), and in the urine of several patients with trophoblastic neoplasms (1) and nontrophoblastic tumors (1,8,11). We have observed that this type of fragment also appears in the urine after infusion of highly purified hCG/B subunit into normal subjects (17) and, therefore, it is a product of the metabolism of hCGI3.…”
Section: Introductionmentioning
confidence: 99%